2006
DOI: 10.1007/s10439-005-9061-9
|View full text |Cite
|
Sign up to set email alerts
|

Design and Control Optimization of Microclimate Liquid Cooling Systems Underneath Protective Clothing

Abstract: The use of protective clothing, whether in space suits, hazardous waste disposal, or sporting equipment, generally increases the risk of heat stress and hyperthermia by impairing the capacity for evaporative heat exchange from the body to the environment. To date the most efficient method of microclimate cooling underneath protective clothing has been via conductive heat exchange from circulating cooling fluid next to the skin. In order to make the use of liquid microclimate cooling systems ((LQ)MCSs) as porta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 73 publications
2
58
0
Order By: Relevance
“…Initial data preparation included computing 1-min mean values from all the iDISK and Tm data recorded every 15 s. All subsequent analyses were conducted using these 1-min mean values. Measurements taken on the body surface demonstrate a response delay in relation to internal changes (12,15). This was confirmed in the present study since initial assessment of iDISK data revealed a response delay in relation to Tm during the rest, exercise, and postexercise periods.…”
Section: Data Preparationsupporting
confidence: 88%
“…Initial data preparation included computing 1-min mean values from all the iDISK and Tm data recorded every 15 s. All subsequent analyses were conducted using these 1-min mean values. Measurements taken on the body surface demonstrate a response delay in relation to internal changes (12,15). This was confirmed in the present study since initial assessment of iDISK data revealed a response delay in relation to Tm during the rest, exercise, and postexercise periods.…”
Section: Data Preparationsupporting
confidence: 88%
“…Typically these garments come in two designs based on heat exchange properties. Active heat exchange garments are cooled by circulating liquid throughout the garment through a tubing network (21,82). Passive heat exchange garments have ice or gel packs that are inserted into the garment to provide the cooling effect (75).…”
Section: Countermeasures To Improve Function In Ms Patients During Thmentioning
confidence: 99%
“…These materials absorb energy during the heating process as phase change takes place, but release their energy to the environment in the phase change range during a reverse cooling process [1][2][3]. Theoretically, PCM's ability to preserve energy is relatively simple.…”
Section: Pcm's Applicationmentioning
confidence: 99%
“…In this way, heat stress is prevented. PCMs in clothing allow the clothing to act as a mediator between the body and the environment, protecting people in hazardous conditions [1][2][3][4][5][6].…”
Section: Pcm's Applicationmentioning
confidence: 99%